2010
DOI: 10.1111/j.1365-2869.2009.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep architecture changes during a trek from 1400 to 5000 m in the Nepal Himalaya

Abstract: SUMMARY The aim of this study was to examine sleep architecture at high altitude and its relationship to periodic breathing during incremental increases in altitude. Nineteen normal, sea level-dwelling volunteers were studied at sea level and five altitudes in the Nepal Himalaya. Morning arterial blood gases and overnight polysomnography were performed in 14 subjects at altitudes: 0, 1400, 3500, 3900, 4200 and 5000 m above sea level. Subjects became progressively more hypoxic, hypocapnic and alkalinic with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 24 publications
5
42
0
3
Order By: Relevance
“…These indicators of disordered breathing during sleep had not improved after 2 weeks at altitude. The acute effects of terrestrial altitude on disordered breathing during sleep have been reported previously, albeit in older participants,14 16 but this is the first study to show that these effects persist for at least 2 weeks. The 10 athletes in this study were split into two equal groups based on the degree to which their breathing during sleep was impaired: five of them were severely affected, and the other five were unaffected, on all three nights of testing at altitude.…”
Section: Discussionsupporting
confidence: 58%
“…These indicators of disordered breathing during sleep had not improved after 2 weeks at altitude. The acute effects of terrestrial altitude on disordered breathing during sleep have been reported previously, albeit in older participants,14 16 but this is the first study to show that these effects persist for at least 2 weeks. The 10 athletes in this study were split into two equal groups based on the degree to which their breathing during sleep was impaired: five of them were severely affected, and the other five were unaffected, on all three nights of testing at altitude.…”
Section: Discussionsupporting
confidence: 58%
“…In a study of 14 trekkers hiking from 1400 m to 5000 m, the central respiratory disturbance index increased progressively from 0/h to 56/h, while obstructive apneic/ hypopneic index reduced over the same period from 11/h to 2/h. 11 Similar observations were made by the same investigators in a group of five patients with moderate OSA at simulated altitude. The AHI due to obstructive apnea at 60 m, 610 m, and 2750 m was 25.5, 17.3, and 0.5, respectively; the AHI from central apnea was 0.38, 8.1, and 78.8, respectively at the same altitudes.…”
Section: Discussionsupporting
confidence: 74%
“…As a result, arterial hypoxemia is attenuated, but hypocapnia typically appears. In this condition, owing to the highly hypoxic environment, arterial oxygen saturation (SaO 2 ) is low and decreases further during sleep [3][4][5]. Periodic breathing (PB) respiration has been described in normal subjects at high altitude during sleep at arrival and up until a 1-month stay [1,4].…”
Section: Introductionmentioning
confidence: 99%